2017
DOI: 10.9734/arrb/2017/34672
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Enzymatic Antioxidants among Breast Cancer Women of African Descent in Sokoto, Nigeria

Abstract: A cross-sectional study was conducted in which patients with confirmed cases of breast cancer and age-and gender-matched apparently healthy individuals were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Similarly, a previous report [50] reported significantly decreased antioxidant enzymes (glutathione peroxidase and superoxide dismutase) and vitamins (vitamin C and vitamin E) in the patients with benign prostate hyperplasia and prostate cancer when compared with the control group (p < 0.005). In another study [18], an increased lipid peroxidation with decreased antioxidant status was observed among breast cancer patients of African Descent in Sokoto, Nigeria. Similarly, a previous report [51] proved that the antioxidant capacity of plasma in chronic obstructive pulmonary disease patients increased about 2 folds as compared with normal subjects measured using the ferric reducing ability of plasma assay.…”
Section: Yes Nomentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, a previous report [50] reported significantly decreased antioxidant enzymes (glutathione peroxidase and superoxide dismutase) and vitamins (vitamin C and vitamin E) in the patients with benign prostate hyperplasia and prostate cancer when compared with the control group (p < 0.005). In another study [18], an increased lipid peroxidation with decreased antioxidant status was observed among breast cancer patients of African Descent in Sokoto, Nigeria. Similarly, a previous report [51] proved that the antioxidant capacity of plasma in chronic obstructive pulmonary disease patients increased about 2 folds as compared with normal subjects measured using the ferric reducing ability of plasma assay.…”
Section: Yes Nomentioning
confidence: 88%
“…In both patients suffering from lung cancer as well as glaucoma, the concentration of MDA is high; thereby validating the reliability of MDA assay to find out oxidative stress in relation to pathology of various diseases [16] [17]. A Study in a tertiary hospital in Nigeria reported lipid peroxidation with a decrease in antioxidant activity [18] among breast cancer patients.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation